Техніко-економічні показники технологій теплової енергетики, що експлуатуються в маневрених режимах - Kobernik V.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
There is a deficit in united energy system of Ukraine of installed capacity of flexible generation units which are able to quickly reach the operating mode, change the power generation levels in a wide range. To model additional measures increasing the flexibility of the power system, it is necessary to know the technical and economic indicators of thermal power technologies and its specific operating modes.The purpose of the article is to determine: efficiency factors depending on the power unit load; start-up costs depending on downtime duration and different fuel prices; the influence of maneuvering modes on lifetime resource indicators; as well as comparison of indicators for various technologies of thermal energy. The following thermal power technologies: natural gas, hard or bituminous coal fired steam turbine supercritical pressure, steam-gas, gas turbine open cycle and gas piston engines. The calculation formulas allowing estimate the influence of the power plant operation mode on the efficiency is obtained. The results of calculation of the start-up specific costs depending from the type of the unit and the idle time is presented. The different values of thermal power unit start-up cost are presented depending on idle time. As an example, the balancing of 660 MW electric power with different equipment composition are considered. The analysis of the results shows that the highest start-up cost is for coal-fired steam turbine plants, and the composition of the equipment with the lowest start-up cost varies depending on the downtime: up to 2 hours, 2 – 5 hours, more than 5 hours. Formulas for recalculating the cost of starting at different fuel prices are obtained. The influence of maneuvering modes on the lifetime resource indicators of thermal power plants is also presented.The conventional thermal power generators of the united energy system of Ukraine have actually overcome their physical capabilities to ensure effective load following, therefore, it is necessary to introduce new highly flexible capacities, and the proposed formulas and results could be helpful to determine the volumes and characteristics of new thermal power plants needed to implement into power system.